Does an individual estimation of halflife improve the results of radioiodine therapy of Graves’ disease? - Schneider, P.; Körber, C.; Körber-Hafner, N.; Hänscheid, H.; Reiners, Chr. (Nuklearmedizin - NuclearMedicine, 2002)
Aim: The impact of our dosimetry concept on radioiodine therapy success in Graves’ disease (GD) was analysed. Three questions arised: Did individual estimation of pretherapeutic halflife improve therapeutic success?. Did individual dosimetry result in accurate dose calculation?. Did antithyroid medication have a measurable influence on therapeutic success under the prevailing conditions?. Methods: 126 consecutive patients were treated with 200 Gy I-131 in our therapy ward for GD and followed-up six to nine months after therapy. Success quote was assessed using a standardized protocol and treatment was classified as successful when the patient was eu- or hypothyroid, or unsuccessful when he or she presented with a suppressed TSH-level or in hyperthyroid condition after antithyroid medication withdrawel. Antithyroid medication, activity I-131, dose, concentration of fT3 and fT4, specific delivered dose and halflife were put into a multiple regression model to assess their influence on therapeutic success. In order to assess possible factors disturbing the therapeutic outcome, relevant parameters were analyzed using Logit transformation. Results: Out of 126 patients 84 were classified as successfully treated and 42 (33,3%) as failures. A significant influence on the outcome only was found for thyroid mass. However, therapeutic success appeared to be more distinctly determined by the specific delivered dose using an estimated halflife of 5.5 days (Odds: 10.0, p <0.001). Accurate intratherapeutic dosimetry did not play a significant role to enhance therapeutic success. Neither did antihyroid medication during radioiodine therapy exert any significant impact. Conclusions: Measurement of individual intratherapeutic halflife as opposed to an estimate using a standard halflife did not provide improved results concerning the target dose. Retrospectively, the therapeutic outcome on the basis of a measured halflife as compared to a standard halflife did not significantly improve. In addition, no influence of antithyroid medication on therapy success was found.
Keywords: Radioiodine therapy; Graves’ disease; dosimetry; specific dose